Auxin Distribution in Lateral Root Primordium Development Affects the Size and Lateral Root Diameter of Rice - Kawai, Tsubasa; Akahoshi, Ryosuke; Shelley, Israt J.; Kojima, Takaaki; Sato, Moeko; Tsuji, Hiroyuki; Inukai, Yoshiaki (Frontiers in Plant Science, 2022)
Lateral roots (LRs) occupy a large part of root system and play a central role in plant water and nutrient uptake. Monocot plants such as rice produce two types of LRs: S-type (short and thin) and L-type (long, thick, and capable of further branching). Because of the ability to produce higher-order branches, L-type LR formation contributes to efficient root system expansion. Auxin plays a major role in regulating root system development, but its involvement in developing different types of LRs is largely unknown. Here, we show that auxin distribution is involved in regulating LR diameter. Dynamin-related protein (DRP) genes were isolated as causative genes of the mutants with increased L-type LR number and diameter than wild-type (WT). In the drp mutants, reduced endocytic activity was detected in rice protoplast and LRs with a decreased OsPIN1b-GFP endocytosis in the protoplast. Analysis of auxin distribution using auxin-responsive promoter DR5 revealed the upregulated auxin signaling in L-type LR primordia (LRP) of the WT and the mutants. Application of polar auxin transport inhibitors enhanced the effect of exogenous auxin to increase LR diameter with upregulated auxin signaling in the basal part of LRP. Inducible repression of auxin signaling in the mIAA3-GR system suppressed the increase in LR diameter after root tip excision, suggesting a positive role of auxin signaling in LR diameter increase. A positive regulator of LR diameter, OsWOX10, was auxin-inducible and upregulated in the drp mutants more than the WT, and revealed as a potential target of ARF transcriptional activator. Therefore, auxin signaling upregulation in LRP, especially at the basal part, induces OsWOX10 expression, increasing LR diameter.